Evaluasi Kandungan Nutrien Bungkil Wijen Lokal Sebagai Bahan Pakan Unggas - Astuti, Isti (Universitas Sebelas Maret (UNS), 2007)
The present study was conducted to evaluate nutrient contents of local sesame meal as feedstuff of poultry. Three varieties of sesame seed were investigated, there were Local Black, S1 and S2. Its founded from Bendosari district, Sukoharjo regency, Central of Java Province. The experimant was done throught proximate analyses in the laboratory of Feed and Animal Nutrition, Departement of Animal Husbandry, Agricultural Faculty, Sebelas Maret University. The result showed that amount of sesame meal between 61,48 to 63,50% from weight of seed. Nutrient composition of Local Black sesame meal was 40,13% crude protein (CP), 20,08% crude fat, 4,64% crude fiber , 10,17% ash and 3212 kcal/kg ME. Nutrient composition of S1 sesame meal was 37,91% CP, 19,12 % crude fat, 6,01% crude fiber, 9,52% ash, 3113 kcal/kg ME whereas nutrient composition of S2 was 39,58% CP, 26,26 % crude fat, 6,21% crude fiber, 7,85% ash and 3195 Kcal/kg ME. The result of this experiment concluded that local sesame meal is generally good as feedstuff protein source in terms of chemical composition based ‘proximate analyses’ especially CP content. Key words : local sesame meal, nutrient contents